Nanoporous trimetallic PdCuAg alloys as efficient electrocatalysts by all-direction accessibility and synergetic effects. Issue 12 (23rd February 2022) - Li, Jun-Xuan; Yin, Hong-Xing; Geng, Qinghong; Du, Dawei; Ma, Lian; Fan, Longlong; Hua, Qingfeng; Li, Cuiling
Abstract : Nanoporous nanoparticles with their surfaces open to reagents enable good electron/mass transport and overall resistance to aggregation, thus they are significantly important in electrocatalytic applications. Abstract : Nanoporous nanoparticles with their surfaces open to reagents enable good electron/mass transport and overall resistance to aggregation, thus they are significantly important in electrocatalytic applications. Herein, a simple yet efficient swelling agent-merging micelle assembly strategy is developed to prepare nanoporous PdCuAg alloys with narrow particle size distributions and tunable chemical compositions. By advancing the advantages of nanoporous constructions and the synergistic alloy effect, the nanoporous Pd68 Cu26 Ag6 nanoparticle exhibits superior electrocatalytic performance toward the ethanol oxidation reaction with a mass activity of 4.0 A mgPd −1 and specific activity of 25.9 mA cm −2 . In addition, the nanoporous PdCuAg alloys are capable of breaking the C–C bond to oxidize ethanol completely.